Adaptive collaborative management: Experiential and theoretical forebearers - Colfer, C.J.P.; Prabhu, R.; Larson, A.M. (Routledge, 2021)
Chapter 1 briefly introduces the concept of and rationale for adaptive collaborative management (or ACM), as implemented by the Center for International Forestry Research (CIFOR) and its partners around the forested tropics. It then provides the professional trajectories of the three editors, an anthropologist, a forester and a natural resource governance specialist, showing how they came to consider this approach of value. Their respective experience in Asia, Africa and Latin America brings geographical and ethnic variety to their observations and conclusions as well. A third section provides the theoretical underpinnings for the approach, drawing heavily on anthropological and systems-oriented thinking. The authors build on theories and observations from the 20th century as well as contemporary approaches. The concluding section briefly introduces each subsequent chapter, laying out the contributing authors’ experience and improvements to the original version of ACM as implemented within CIFOR’s programmes.